NILAI EKONOMI EKOWISATA TAMAN NASIONAL TESSO NILO DENGAN PENDEKATAN METODE CONTINGENT VALUATION DIKECAMATAN UKUI KABUPATEN PELALAWAN - Desriani, Juria; Putro, Tri Sukirno; Iyan, Rita Yani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at the tourist attraction of Ecotourism Tesso Nilo National Park where is located in District Ukui Pelalawan. This research aims to know how the visitor’s assesment about the Tesso Nilo National ParkDistrict Ukui Pelalawanand where thevisitor’s comes bye. This research also aims to know the economic value of Ecotourism Tesso Nilo National Park with Contingent Valuation Method approach in District Ukui Pelalawan.Total population used as samples in this research were 89 people. The method used in this research isaccidental sampling methode. The analytical method used in thisresearch is descriptive method using Contingent Valuation Method.From the results of this research concluded that general assesment visitor against the Tesso Nilo National Park EcotourismDistrict Ukui Pelalawan is pretty good. It can be seen from the highest visitor answers bye62,92 %.The origin of theMajority of visitors are still coming from inside the Subdistrict Ukui. Economic value of Ecotourism Tesso Nilo National Park with Contingent Valuation Method approach in District Ukui Pelalawan, thatcan be foundfrom the total income of Willingness To Pay (WTP) visitors to the Government SubdistrictUkui is Rp. 792.424 per month. The amountwill increase onholidays.Keywords : The Economic Value of Ecotourism, and Contingent Valuation Methods